Experimental study on the behaviour of an electrorheological double miniature valve. (July 2021) - Bauerochs, Tobias; Ulrich, Stephan; Bruns, Rainer
In many hydraulic systems, actuators are controlled by conventional valves that require a lot of installation space. They consist of many moving parts which make them prone to errors. Miniature valves with high power densities using the electro-rheological technology can help to reduce the space requirement and possible defects. They can generate a local and reversible viscosity increase to realize higher usable pressure drops. Until now, some valves using this working principle are macro-scaled for the use in conventional hydraulics and needed too much space. Others are microvalves for microfluidics and therefore could not generate a sufficiently high pressure drop. Intermediary sizes such as miniature valves combined with conventional hydraulics have not yet been developed satisfactorily. For this reason, a medium-sized valve was designed to be used in conventional hydraulics but requires considerably less space. Furthermore, it is manufacturable using conventional production methods. The proof of function of this new miniature valve confirmed the concept. Experiments showed that the measured ER behaviour is similar to previous results of macro scale ER valves. The valve reproducibly generated pressures of more than 5 bar without any leakage. This proved that a valve with this novel design is usable in conventional hydraulic systems.